EKSTRAKSI DNA DARI SPERMA PADA KONDOM DAN KAIN YANG TERSIMPAN SAMPAI DUA BELAS HARI - Jehuda, Vandus (SIMBIOSIS, 2013)
Sperm is a biological material that is often used as evidence in rape cases. The research of DNA extraction from sperm was conducted in order to determine DNA whether it could be extracted from sperm in the condom and fabrics that were stored for 3, 6, 9, and 12 days and to know the success of its amplification. The sample is dripped into a condom and fabrics each 150 ?L, then stored for 3, 6, 9, and 12 days. DNA extraction was performed using phenol-chloroform method that had been modified and DNA amplification using PCR Mastermix. The results showed that DNA could be extracted and the extraction could be amplified from sperm in the condom and fabrics that were stored for 3, 6, 9 and 12 days.